IL‐36γ is secreted in microparticles and exosomes by lung macrophages in response to bacteria and bacterial components. Issue 2 (10th February 2016) - Kovach, Melissa A.; Singer, Benjamin H.; Newstead, Michael W.; Zeng, Xianying; Moore, Thomas A.; White, Eric S.; Kunkel, Steven L.; Peters‐Golden, Marc; Standiford, Theodore J.
Abstract : Cellular sources and secretion mechanisms of IL‐36γ in response to recombinant bacterial components and whole bacteria. Abstract : Interleukin‐36 is a family of novel interleukin‐1‐like proinflammatory cytokines that are highly expressed in epithelial tissues and several myeloid‐derived cell types. Like those of classic interleukin‐1 cytokines, the secretion mechanisms of interleukin‐36 are not well understood. Interleukin‐36γ secretion in dermal epithelial cells requires adenosine 5'‐triphosphate, which suggests a nonclassical mechanism of secretion. In this study, murine pulmonary macrophages and human alveolar macrophages were treated with recombinant pathogen‐associated molecular patterns (intact bacteria: Klebsiella pneumoniae or Streptococcus pneumoniae ). Cell lysates were analyzed for messenger ribonucleic acid by quantitative real‐time polymerase chain reaction, and conditioned medium was analyzed for interleukin‐36γ by enzyme‐linked immunosorbent assay, with or without sonication. In addition, conditioned medium was ultracentrifuged at 25, 000 g and 100, 000 g, to isolate microparticles and exosomes, respectively, and interleukin‐36γ protein was assessed in each fraction by Western blot analysis. Interleukin‐36γ mRNA was induced in both murine and human lung macrophages by a variety of pathogen‐associated molecular patterns, as well as heat‐killed and live Klebsiella pneumoniae and Streptococcus pneumoniae, and induction occurred in a myeloid differentiation response gene 88–dependent manner. Secretion of interleukin‐36γ protein was enhanced by adenosine 5'‐triphosphate. Furthermore, extracellular interleukin‐36γ protein detection was markedly enhanced by sonication to disrupt membrane‐bound structures. Interleukin‐36γ protein was detected by Western blot in microparticles and exosome fractions isolated by ultracentrifugation. Interleukin‐36γ was induced and secreted from lung macrophages in response to Gram‐negative and ‐positive bacterial stimulation. The results suggest that interleukin‐36γ is secreted in a non‐Golgi–dependent manner by lung macrophages in response to Gram‐positive and ‐negative bacterial challenge.